Financing Negative Shocks: Evidence from Hurricane Harvey - Collier, Benjamin L.; Powell, Lawrence S.; Ragin, Marc A.; You, Xuesong (Journal of Financial and Quantitative Analysis, 2025)
We examine the effects of a severe climate event on local firms. Our data include 8,218 business credit reports and a detailed survey of 273 businesses in the area affected by Hurricane Harvey. Delinquent credit balances doubled in areas with the worst flooding, although nonflooded areas also had significant credit impairments. Only independent businesses showed signs of distress; subsidiaries of larger firms did not. Firms were largely uninsured and often were denied credit postdisaster. Many funded recovery informally, such as through friends and family. Our findings suggest that several financial frictions compound the challenges posed by a severe climate event.